2019
DOI: 10.1002/jcb.29489
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key microRNAs and hub genes in non‐small‐cell lung cancer using integrative bioinformatics and functional analyses

Abstract: Non-small-cell lung cancer (NSCLC) is an extremely debilitating respiratory malignancy. However, the pathogenesis of NSCLC has not been fully clarified.The main objective of our study was to identify potential microRNAs (miRNAs) and their regulatory mechanism in NSCLC. Using a systematic review, two NSCLC-associated miRNA data sets (GSE102286 and GSE56036) were obtained from Gene Expression Omnibus, and the differentially expressed miRNAs (DE-miRNAs) were accessed by GEO2R. Survival analysis of candidate DE-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Recently, Chen et al (18) demonstrated that silencing miR-126 could reverse the anticancer effects of naringin on NSCLC cell growth, in which naringin induces a reduction in the phosphatidylinositol-3 protein kinase (PI3K)/protein kinase B (AKT)/mechanistic target of rapamycin and suppresses vascular cell adhesion molecule 1 protein levels. In addition, miR-126 exhibits a suppressive effect on NSCLC cell invasion by interacting with three hub genes: VEGFA, AKT1, and Kirsten rat sarcoma viral oncogene homologue (19). Additionally, other studies have demonstrated that miR-126 can suppress the growth, migration and invasion of NSCLC cells by targeting chemokine (C-C motif) receptor 1 and solute carrier family 7 (cationic amino acid transporter, y+ system) member 5 (SLC7A5) or v-crk sarcoma virus CT10 oncogene homologue (Crk) (20)(21)(22)(23), indicating that miR-126 may control the growth of lung cancer cells through multiple targets (Table Ⅰ).…”
Section: Mir-126 and Lung Cancer Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chen et al (18) demonstrated that silencing miR-126 could reverse the anticancer effects of naringin on NSCLC cell growth, in which naringin induces a reduction in the phosphatidylinositol-3 protein kinase (PI3K)/protein kinase B (AKT)/mechanistic target of rapamycin and suppresses vascular cell adhesion molecule 1 protein levels. In addition, miR-126 exhibits a suppressive effect on NSCLC cell invasion by interacting with three hub genes: VEGFA, AKT1, and Kirsten rat sarcoma viral oncogene homologue (19). Additionally, other studies have demonstrated that miR-126 can suppress the growth, migration and invasion of NSCLC cells by targeting chemokine (C-C motif) receptor 1 and solute carrier family 7 (cationic amino acid transporter, y+ system) member 5 (SLC7A5) or v-crk sarcoma virus CT10 oncogene homologue (Crk) (20)(21)(22)(23), indicating that miR-126 may control the growth of lung cancer cells through multiple targets (Table Ⅰ).…”
Section: Mir-126 and Lung Cancer Tumorigenesismentioning
confidence: 99%
“…In the past decade, a large number of studies have documented that miR-126 may also be a meaningful prognostic marker of lung cancer (19,21,(63)(64)(65) (Table II). Recently, Xu et al (66) found that high plasma expression level of miR-126 in patients with lung cancer was associated with shorter disease-free survival [hazard ratios (HRs) of univariate Cox and multivariate Cox were 1.867 and 1.582, respectively; 95% confidence intervals (CIs) of univariate Cox and multivariate Cox were 1.386-2.515 and 1.158-2.161, respectively] and overall survival (OS) (HRs of univariate Cox and multivariate Cox were 1.706 and 1.320, respectively; 95% CIs of univariate Cox and multivariate Cox were 1.218-2.388 and 0.932-1.817, respectively).…”
Section: Mir-126 and Lung Cancer Prognosismentioning
confidence: 99%
“…Propofol also inhibits the progression of NSCLC by regulating the expression level of some miRNAs, including miR-372 (13), miR-1284 (14) and miR-486 (15). As an important oncogene in NSCLC, a higher miR-21-5p level is associated with recurrence (38), tumor stage (39) and poor overall survival (40) of patients with NSCLC. The link between Fpropofol and miR-21 has been reported in several diseases, but not in NSCLC.…”
Section: Mapk10 Expression -----------------------------mentioning
confidence: 99%
“…Using bioinformatic analysis, miRNAs that exhibit oncogenic activity in carcinogenesis have been identified, including miR-21 [10], miR-155 [11], and miR-142 [12]. Literature indicates that miR-31-5p is overexpressed in diverse tumor types [13], and studies have explored its role in lung and breast cancer AGING metastasis [14,15]. However, the underlying mechanisms of the role of miR-31-5p in COAD remain unknown.…”
Section: Introductionmentioning
confidence: 99%